Narrative-Quantitative ESG Disclosure, AI-assisted Sustainability Reporting dan Nilai Perusahaan - Dwi Nova Wijaya; Rommy Mochamad Ramdhani; Dewi Fitrotus Sa’diyah (LPPM-STPI, 2026)
This study examines the impact of narrative-quantitative ESG disclosure and the role of AI-assisted sustainability reporting on firm value in Indonesia. Utilizing panel data of 3,794 observations from companies listed on the Indonesia Stock Exchange during 2018-2024 with multiple regression methods, the research measures ESG disclosure characteristics through textual analysis and estimates their impact on Tobin's Q. Results reveal that quantitative ESG disclosure significantly enhances firm value, while narrative disclosure demonstrates no substantial impact on market valuation. The adoption of artificial intelligence technology in sustainability reporting transforms this relationship dynamic, whereby narrative disclosure becomes a significant factor increasing firm value, whereas the superiority of quantitative disclosure diminishes. The dominance of narrative elements over quantitative data consistently reduces firm value as investors appreciate information balance. AI technology functions as a validation mechanism that strengthens the credibility of narrative elements through reducing information asymmetry and enhancing sustainability reporting transparency.